Penerapan Proses Rehabilitasi pada Penyalahguna Narkotika sebagai Upaya Pemulihan - Bastianto Nugroho; Siti Rahayu; M. Roesli; Reinhard Yeremia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2021)
Abstract Narcotics are substances or drugs that are very useful and necessary for the treatment of certain diseases. However, if it is misused or used not in accordance with the standard of treatment it can have very detrimental consequences for individuals or society, especially the younger generation. This will be more detrimental if accompanied by the abuse and illicit trafficking of narcotics which can result in a greater danger to the life and cultural values of the nation which in turn can weaken national resilience. In its development, Law No. 22/1997 on Narcotics is deemed unable to answer the many aspects of the narcotics problem. One of them is recognizing the negative impact on public health who are in the position of perpetrators, users, and victims of narcotics abuse. In response to this, the Government then established Law Number 35 of 2009 concerning Narcotics. The law aims to find a balance point between the public health approach and the implementation of criminal instruments in overcoming narcotics crime. This research is a normative juridical research, namely research that describes in detail the social phenomena that are the main problems in everyday life associated with the applicable positive criminal law regulations. A normative legal research is intended to provide data as accurate as possible on the crime of narcotics abuse.